Communication Through Hashtags in Social Movements: A Systematic Literature Review - Kharisma Natalia; Sylvana Virgina Agustya; Irwansyah Irwansyah (Borong Newinera Publisher, 2023)
The hashtag #MeToo was launched by activist Tarana Burke in 2006 to create